აბსტრაქტულ-ფიგურატიული მეტარეალიზმის დეკლარაცია: სახვითი ხელოვნების თანამედროვე მიმდინარეობის შემდგომი კვლევა და ანალიზი - გაიანე მანასიანი (World Scientific Reports, 2026)
The present article consolidates and expands my prior research, analysis, and findings related to the formulation of Abstract-Figurative Metarealism — a contemporary fine art movement. Although the concept of metarealism had previously appeared in philosophical and cultural theory, it had not been scientifically defined as a distinct fine art movement. After publishing my first scientific publication on Abstract-Figurative Metarealism in 2024, followed by a second one in 2025, the given 2026 study further examines the movement’s conceptual foundations through theoretical inquiry, comparative analysis with realism, surrealism, magic realism, abstraction, and reflection on artistic practice. Abstract-Figurative Metarealism is defined as an approach that does not negate reality but reveals its multilayered structure by integrating rational and irrational perception, abstraction and figuration, and the unconscious, preconscious, conscious, and — most importantly — superconscious levels of experience. The article suggests that this art movement represents a distinct mode of artistic thinking and intuitive insight rather than a stylistic hybrid. Abstract-Figurative Metarealism positions art as a form of research and knowledge production. By consolidating theoretical discourse and artistic methodology, the study situates Abstract-Figurative Metarealism within contemporary art as an evolving and independent fine art movement.